Calculation of stable operation of vortex spray countercurrent mass exchange device (VSCMED) depending on hydrodynamic characteristics of gas-drop flow - Abdullah, Jalal Mohammed; Al Hayat, Nadim Qasim Mohammed (Technology audit and production reserves, 2014)
The paper gives the method of selecting stable operation modes of the vortex spray countercurrent mass exchange device (VSCMED), which includes calculating the flow of drops taking into account flow uniformity and mutual influence. In order to make the calculation, a number of assumptions, which allow to calculate the device for specific conditions, was introduced. When developing techniques, the impact of forces on the motion of the drop was taken into account. As a result of theoretical and practical studies, the flow rate of gas and droplets, the ratio of centrifugal forces and the forces of aerodynamic drag were determined, thus having ensured the optimum mode of stable operation of VSCMED. The results obtained allow to design new models of VSCMED-type devices when developing new productions for the chemical and petrochemical industries.